2012
DOI: 10.3109/1547691x.2011.642418
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel promotes differentiation of myeloid-derived suppressor cells into dendritic cellsin vitroin a TLR4-independent manner

Abstract: Myeloid cells play a key role in the outcome of anti-tumor immunity and response to anti-cancer therapy, since in the tumor microenvironment they may exert both stimulatory and inhibitory pressures on the proliferative, angiogenic, metastatic, and immunomodulating potential of tumor cells. Therefore, understanding the mechanisms of myeloid regulatory cell differentiation is critical for developing strategies for the therapeutic reversal of myeloid derived suppressor cell (MDSC) accumulation in the tumor-bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 52 publications
1
100
2
2
Order By: Relevance
“…MDSCs have been shown to differentiate into mature macrophages, DCs or granulocytes upon the administration of all-trans-retinoic acid (ATRA) [28,102] or ultra-low noncytotoxic doses of paclitaxel [103]. Although retinoic acid receptors (RARs and RXRs) are known to be expressed on various cell types, receptors RARα and RXRα were detected predominantly on myeloid cells [104].…”
Section: Inhibiting Immunosuppressive Functions Of Mdscsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDSCs have been shown to differentiate into mature macrophages, DCs or granulocytes upon the administration of all-trans-retinoic acid (ATRA) [28,102] or ultra-low noncytotoxic doses of paclitaxel [103]. Although retinoic acid receptors (RARs and RXRs) are known to be expressed on various cell types, receptors RARα and RXRα were detected predominantly on myeloid cells [104].…”
Section: Inhibiting Immunosuppressive Functions Of Mdscsmentioning
confidence: 99%
“…These changes were associated with a partial recovery of tumorspecific T cell responses that were resulted in profound antimelanoma effects indicated by a delayed tumor growth and prolonged animal survival (V.U.,A.S., unpublished results). To decipher the molecular mechanisms of MDSC inhibition under ultra-low paclitaxel treatment, MDSCs were generated in vitro from the bone marrow precursors and treated paclitaxel at ultra-low, nanomolar concentrations [103]. Under these conditions, paclitaxel failed to impair the MDSC generation from bone marrow precursors or to stimulate MDSC apoptosis, whereas the differentiation of these cells towards DCs was found to be significantly stimulated in the toll-like receptor 4-independent way.…”
Section: Inhibiting Immunosuppressive Functions Of Mdscsmentioning
confidence: 99%
“…Hence, injection of tumor cells in combination with CD11b + Gr1 + cells in mice prompt tumor growth [249]. Accordingly, depletion of Gr1 + cells in tumor-bearing mice leads to delayed tumor growth, suggesting MDSC as potential targets for anti-cancer therapy [250][251][252][253][254][255][256]. A report by Youn and colleagues indicated that CD11b + Gr1 + cells from naïve tumor-free mice are not immune suppressive [243].…”
Section: Myeloid Derived Suppressor Cells (Mdsc)mentioning
confidence: 99%
“…For example, both in vitro and in animal models, all trans-retinoid acid (ATRA) has been used to induce MDSC differentiation into mature myeloid cells (Kusmartsev et al 2008;Mirza et al, 2006). More recently, paclitaxel (at ultra-low non-cytotoxic doses) was shown to stimulate differentiation of MDSC into DC (Michels et al, 2012). Another method to reduce MDSC counts was the use of cytostatic agents like gemcitabine; in a mouse model, this drug was shown to reduce GR-1 þ /CD11b þ MDSC levels (Le et al, 2009;Suzuki et al, 2005).…”
Section: Myeloid-derived Suppressive Cells (Mdsc)mentioning
confidence: 99%